Characterization of Full-Length and Truncated Recombinant κ-Carrageenase Expressed in Pichia pastoris - Yu, Yuan; Liu, Zhemin; Yang, Min; Chen, Meng; Wei, Zhihan; Shi, Lixia; Li, Li; Mou, Haijin (Frontiers in Microbiology, 2017)
κ-Carrageenase belongs to glycoside hydrolase family 16 and cleaves the β-(1→4) linkages of κ-carrageenan. In this study, genes encoding the full-length (cgkZ), Por secretion tail-truncated (cgkZΔPst) and carbohydrate binding domain-truncated (cgkZΔCBM) κ-carrageenase proteins were expressed in Pichia pastoris. The copy numbers of gene cgkZ, cgkZΔPst and cgkZΔCBM were 7, 7 and 6, respectively. The enzymatic activities of recombinant enzymes cgkZ, cgkZΔPst and cgkZΔCBM reached 4.68, 5.70, and 3.02 U/mL, respectively, after 120 h of shake flask fermentation at 22℃ and pH 6 in the presence of 1 % (v/v) methanol. The molecular weights of recombinant cgkZ, cgkZΔPst, and cgkZΔCBM were approximately 65, 45 and 40 kDa; their Km values were 2.07, 1.85 and 1.04 mg/mL; and they exhibited optimal activity at 45-50℃ and pH 6-7. All the recombinant enzymes were stimulated by Na+, Mg2+, Ca2+, and dithiothreitol. The end-products of enzymatic hydrolysis were mainly composed of κ-carrageenan tetrasaccharide and hexasaccharide. The removal of the Por secretion tail of κ-carrageenase promoted the transcription of κ-carrageenase gene, enhancing the specific activity of κ-carrageenase without significantly changing its catalytic properties. Although the transcription level of κ-carrageenase gene after the removal of the carbohydrate binding domain was relatively high, the specific activity of the recombinant enzyme significantly decreased. The comprehensive application of the P. pastoris expression system combined with the rational modification of genes may provide a novel approach for the heterologous expression of various marine enzymes with high activities.